Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 - Hildana Aprilia; Eni Wuryani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2021)
This study aims to examine the effect of good corporate governance on company performance in manufacturing companies spread across Indonesia. Measurement of good corporate governance indicators, independent board of commissioners, board of directors, managerial ownership, institutional ownership, and foreign ownership. The measurement of company performance uses the Tobin's Q ratio. The population used of all manufacturing companies in Indonesia listed on the IDX in 2017-2019 is 53 companies. The sampling technique used is purposive sampling method. Testing the hypothesis used multiple linear regression analysis, simultaneous significance test (F test), and individual parameter significance test (t test). The results of the simultaneous statistical significance test (F test) show that the five independent variables have a significant effect on company performance. The results of the statistical significance test of the individual parameters (t test) of the independent board of commissioners variable and institutional ownership have a significant effect on company performance, while the t test results on the variables of the board of directors, managerial ownership, and foreign ownership have no significant effect on company performance.